Analysis of the Application of the Problem Based Learning Model in Multi-Grade Teaching Courses (PKR) at PGSD UMN Al Washliyah Medan - Nurmairina, Nurmairina; Mardhatillah , Mardhatillah; Hasanah, Hasanah; Lestari , Nila; Siregar, Nurhafni (Teunuleh Publisher, 2024)
students, especially the PGSD study program, so that students understand multigrade learning well, a problem based learning model is used. From the application of the problem based learning model, it will be analyzed how PGSD UMN AL Washliyah students understand multi-grade learning subjects. This research was conducted on multi-grade learning courses and analyzed the results of applying the problem based learning model to PGSD students. From the research results, it is known that lecturers have implemented the problem based learning model in accordance with the syntax of the Problem Based Learning model. The student scores include 75% of students getting very good scores and 20% of students getting good scores. While 2.5% of students got quite good grades and 2.5% of students got fair grades. From the results of this research, it can be seen that the Problem Based Learning model can improve student learning outcomes by